Nacella concinna - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA CONCINNA (STREBEL, 1908) (FIG. 8) Patella polaris Hombron & Jacquinot, 1841: 191 (not of Röding, 1798); Martens & Pfeffer, 1886: 101, pl. 2, figs 11–13; Melvill & Standen, 1907: 124. Nacella polaris – Pilsbry, 1891: 120, pl. 49, figs 21–27; Lamy, 1906: 10, Lamy, 1911: 26. Nacella aenea var. polaris – Pelseneer, 1903: 14. Patinella polaris – Strebel, 1908: 81, pl. 5, figs 79–82. Patinella polaris var. concinna Strebel, 1908: 81, pl. 5, fig. 77. Lepeta depressa Hedley, 1916: 42, pl. 6, fig. 64; Arnaud, 1972: 114; Dell, 1972: 32, figs 19, 24–25; Egorova, 1982: 14, fig. 75. Nacella ( Patinigera ) polaris – David, 1934: 127; Zelaya, 2005: 111, fig. 2. Patinigera polaris – Powell, 1951: 82; Walker, 1972: 49; Castellanos & Landoni, 1988: 25, pl. 4, fig. 8. Patinigera polaris concinna – Powell, 1951: 83; Castellanos & Landoni, 1988: 26, pl. 4, fig. 5. Nacella ( Patinigera ) concinna – Powell, 1973: 193–195, pl. 175, figs 1–5; Picken, 1980: 71; Ramírez 1981: 58; 71; Picken & Allan, 1983: 273; Brêthes et al ., 1984: 161; González-Wevar et al. , 2010: 116; González-Wevar et al. , 2011b: 220. Patinigera polaris polaris – Castellanos & Landoni, 1988; 26, pl. 4, fig. 8. Nacella concinna – Beaumont & Wei, 1991: 443; Linse et al. , 2006: 997; de Aranzamendi et al. , 2008: 875; Hoffman et al. , 2010a: 287; 2010b: 765; 2011: 55; 2012a: 922; 2012b: 1; 2013: 1; González-Wevar et al. , 2013: 5221; 2017: 863; Rosenfeld et al. 2017: 3. Nacella cf. concinna – Hain & Melles, 1994: 36, fig. 4.1. Nacella polaris concinna – Aldea, Olabarria & Troncoso, 2008: 355; Aldea & Troncoso, 2009; 49, fig. 2. Nacella polaris polaris – Aldea et al. , 2008: 49, fig. 3. Material studied: Rothera Station, Adelaide Island, Antarctic Peninsula (67°34’03.17’’ S, 68°07’17.40’’ W) N = 50; South Bay, Anvers Island (64°53’21.55’’ S, 63°35’43.44’’ W) N = 40; Yelcho Station, Doumer Island, Palmer Archipelago, Antarctic Peninsula (64°53’34.29’’ S, 63°35’09.04’’ W) N = 40; Covadonga Bay, Antarctic Peninsula (63°19’13.96’’ S, 57°53’54.15’’ W) N = 50, James Ross Island, East Antarctic Peninsula (63°55’14.33’’ S, 57°15’54.22’’ W) N = 40, Hannah Point, Livingstone Island, South Shetland Islands (62°39’11.31’’ S, 60°36’55.44’’ W) N = 40; Fildes Bay, King George Island, South Shetland Islands (62°12’28.68’’ S, 58°57’24.89’’ W) N = 80, Admiralty Bay, King George Island, South Shetland Islands (62°05’14.40’’ S, 58°27’29.57’’ W) N = 80; Deception Island (62°55’14.52’’ S, 60°35’14.62’’ W) N = 50; Elephant Island (61°05’12.24’’ S, 55°20’22.54’’ W) N = 29; South Orkney Island (60°44’20.03’’ S, 44°44’17.05’’ W) N = 26; Signy Island, South Orkneys Islands (60°43’22.22’’ S, 45°35’16.14’’ W) N = 30; South Georgia (54°17’00.11’’ S, 36°29’13.04’’ W) N = 100. Shell: The shell shape and sculpture are very variable (Beaumont & Wei, 1991; de Aranzamendi et al. , 2008; Hoffman et al ., 2010b; González-Wevar et al. , 2011b) (Fig. 8A–C). The species exhibits a conical morphology, dorsally raised, with a thick and non-translucent shell (Fig. 8A–F). The anterior part of the animal is laterally compressed (Fig. 8D–F). It has a large shell (maximum length 120 mm) and a variable profile (Fig. 8A–C). The apex is situated at the anterior 30–40% of the shell’s length (Fig. 8A–C). All the slopes of the shell are convex (Fig. 8D–F). The aperture of the shell is oval. The surface of the shell is sculptured with weak primary radial ribs, weaker secondary ones and concentric growth lines. The margin of the shell is highly crenulated. The external coloration is very variable (pale brownish/green/grey to dark brown and black). The internal part of the shell varies from creamy nacreous to dark bronzy-brown with dark lines corresponding to external colour patterns. External anatomy: The ventral area of the foot is black and the epipodial fringe is highly recognizable. The mantle fold is thick and dun-brown coloured. The mantle tentacles are in alternate series of a single black longer tentacle and three shorter ones (white/black/white) (Fig. 8G). The cephalic tentacles are dorsally pigmented with a black line (Fig. 8G). Radula: The first lateral teeth are set close together on the anterior edge of the basal plates, of medium length and with two spoon-like cusps. The second laterals are broader, wider spaced, with two spoonlike cusps. One of them is very small and the other is bigger and broader (Fig. 8H). Distribution: Maritime Antarctica, including ice-free rocky ecosystems of the Antarctic Peninsula, the South Shetland Islands, South Georgia, South Orkneys, Bouvet, Elephant Island, Seymour Island, Paulet Island, Wander Island, Anvers Island and Peterman Island (Fig. 8I). Habitat: Intertidal and subtidal between 0 and 150 m depths. Comments: The Antarctic limpet represents a single genetic population along maritime Antarctica (González-Wevar et al. , 2011b, 2013, 2016b, 2017), but thispopulationdifferesmarkedlyfromthosefromSouth Georgia (González-Wevar et al. , 2013). The inter- and subtidal morphotypes were once regarded as separate subspecies, N. polaris polaris and N. polaris concinna (Powell, 1951). Nevertheless, genetic comparisons using allozymes (Beaumont & Wei, 1991), mtDNA (González-Wevar et al. , 2011b, 2013, 2016b) and AFLPs (Hoffman et al ., 2010b) confirmed that these forms represent a single evolutionary unit. Accordingly, shell height, shape and sculpture differences in the Antarctic limpet represent phenotypic plasticity in the species. : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on pages 317-320, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Strebel H. 1908. Die Gastropoden (mit Ausnahme de nackten Opisthobranchier). Wissenschaftliche Ergebnisse der Schwedischen Sudpolar-Expedition 1901 - 1903 6: 1 - 111.", "Hombron JB, Jacquinot CH. 1841. Description de quelques Mollusques provenant de la campagne de l'Astrolabe et de la Zelee. Annales des Sciences Naturelles Zoologie 16: 190 - 192.", "Martens E, Pfeffer G. 1886. Die Mollusken von Sud-Georgien. Jahrbuch der Hamburgischen Wissenschaftlichen Anstalten 3: 65 - 135.", "Melvill JC, Standen P. 1907. The marine Mollusca of the Scottish National Antarctic Expedition. Transactions of the Royal Society of Edinburgh 46: 119 - 157.", "Pilsbry HA. 1891. Manual of conchology. Structural and systematic with illustrations of the species, Vol. 13. Philadelphia, PA: Academy of Natural Sciences.", "Lamy E. 1906. Sur quelques Mollusques des Orcades du Sud. Bulletin du Museum d'histoire naturelle Paris 1: 121 - 126.", "Lamy E. 1911. Sur quelques Mollusques de la George du Sud, et des iles Sandwich du Sud. Bulletin Museum of Paris 22 - 27.", "Pelseneer P. 1903. Expedition Antarctique Belge 1897 - 1899 Zoologie. Mollusques (Amphineura, Gastropodes et Lamellibranches). Resultats du Voyage S. Y. Belgica. Rapports Scientifiques publies aux frais du gouvernement belge, sous la direction de la commission de la Belgica. Anvers Zoology 1 - 85.", "Hedley C. 1916. Report on Mollusca from elevated marine beds ' Raised Beaches' of McMurdo Sound. British Antarctic Expedition 1907 - 1909, Geology 2: 85 - 88.", "Arnaud PM. 1972. Invertebres marins des XIIe et XVe Expeditions Antarctiques Francaises en Terre Adelie. 8. Gasteropodes Prosobranches. Tethys 4: 3 - 8.", "Dell RK. 1972. Notes on nomenclature of some Mollusca from Antarctica and southern South America. Records of the Dominion Museum 8: 21 - 42.", "Egorova EN. 1982. Biological results of the Soviet Antarctic expeditions, 7, Mollusca of the Davis Sea. Explorations of the Faunas of the Seas 26: 1 - 142.", "David L. 1934. Zoologische Ergebnisse der Reisen von Dr. Kohl- Larsen nach den subatnarktischen Inseln bei Neuseeland und nach Sudgeorgien. Senckenbergiana 16: 126 - 137.", "Zelaya D. 2005. Systematics and biogeography of marine gastropod molluscs from South Georgia. Spixiana 28: 109 - 139.", "Powell AWB. 1951. Antarctic and Subantarctic Mollusca: Pelecypoda and Gastropoda. Discovery Reports 26: 47 - 196.", "Walker A. 1972. Introduction to the ecology of the antarctic limpet Patinigera polaris (Hombron and Jaquinot) at Signy Island, South Orkneys Islands. Antarctic Survey Bulletin 28: 49 - 69.", "Castellanos ZJA, Landoni N. 1988. Catalogo descriptivo de la malacofauna marina magallanica 2 Archaeogastropoda. Comision de Investigaciones Cientificas de la Provincia de Buenos Aires (CIC).", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Picken G. 1980. Distirbution, growth, and reproduction of the Antarctic limpet Nacella (Patinigera) concinna (Strebel, 1908). Journal of Experimental Marine Biology and Ecology 42: 71 - 85.", "Ramirez J. 1981. Moluscos de Chile. Vol. 1 Archeogastropoda. Chile: Museo Nacional de Historia Natural. 1 \u00aa Edicion. Santiago, Chile.", "Picken G. Allan D. 1983. Unique spawning behaviour in the Antarctic limpet Nacella (Patinigera) concinna (Strebel, 1908). Journal of Experimental Marine Biology and Ecology 71: 283 - 287.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, David B, Poulin E. 2011 b. Phylogeography and demographic inference in Nacella (Patinigera) concinna (Strebel, 1908) in the western Antarctic Peninsula. Deep-Sea Research Part II: Topical Studies in Oceanography 58: 220 - 229.", "Beaumont AR, Wei JHC. 1991. Morphological and genetic variation in the Antarctic limpet Nacella concinna (Strebel, 1908). Journal of Molluscan Studies 57: 443 - 450.", "Linse K, Griffiths HJ, Barnes DKA, Clarke A. 2006. Biodiversity and biogeography of Antarctic and sub-Antarctic mollusca. Deep Sea Research Part II: Topical Studies in Oceanography 53: 985 - 1008.", "de Aranzamendi MC, Sahade R, Tatian M, Chiappero MB. 2008. Genetic differentiation between morphotypes in the Antarctic limpet Nacella concinna as revealed by inter-simple sequence repeat markers. Marine Biology 154: 875 - 885.", "Hoffman JI, Clarke A, Linse K, Peck LS. 2010 a. Effects of brooding and broadcasting reproductive modes on the population genetic structure of two Antarctic gastropod molluscs. Marine Biology 158: 287 - 296.", "Hoffman JI, Peck LS, Hillyard G, Zieritz A, Clark MS. 2010 b. No evidence for genetic differentiation between Antarctic limpet Nacella concinna morphotypes. Marine Biology 157: 765 - 778.", "Hoffman JI, Peck LS, Linse K, Clarke A. 2011. Strong population genetic structure in a broadcast-spawning Antarctic marine invertebrate. The Journal of heredity 102: 55 - 66.", "Hoffman JI, Clark MS, Amos W, Peck LS. 2012 a. Widespread amplification of amplified fragment length polymorphisms (AFLPs) in marine Antarctic animals. Polar Biology 35: 919 - 929.", "Hoffman JI, Clarke A, Clark MS, Fretwell P, Peck LS. 2012 b. Unexpected fine-scale population structure in a broadcast-spawning Antarctic marine mollusc. PLoS ONE 7: e 32415.", "Hoffman JI, Clarke A, Clark MS, Peck LS. 2013. Hierarchical population genetic structure in a direct developing Antarctic marine Invertebrate. PLoS ONE 8: e 63954.", "Gonzalez-Wevar CA, Saucede T, Morley SA, Chown SL, Poulin E. 2013. Extinction and recolonization of maritime Antarctica in the limpet Nacella concinna (Strebel, 1908) during the last glacial cycle: toward a model of Quaternary biogeography in shallow Antarctic invertebrates. Molecular Ecology 22: 5221 - 5236.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Rosenfeld S, Aldea C, Ojeda J, Marambio J, Hune M, Troncoso J, Mansilla A. 2017. Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance. Polar Research 36: 1 - 10.", "Hain S, Melles M. 1994. Evidence for a marine molluscan fauna beneath ice shelves in the Lazarev and Weddell seas, Antarctica, from shells of Adamussium colbecki and Nacella (Patinigera) cf concinna. Antarctic Science 6: 29 - 36.", "Aldea C, Olabarria C, Troncoso J. 2008. Bathymetric zonation and diversity gradient of gastropods and bivalves in West Antarctica from the South Shetland Islands to the Bellingshausen Sea. Deep Sea Research Part I: Oceanographic Research Papers 55: 350 - 368.", "Aldea C, Troncoso J. 2009. Systematics and distribution of shelled molluscs (Gastropoda, Bivalvia and Scaphopoda) from the South Shetland Islands to the Bellingshausen Sea, West Antarctica. Iberus 26: 43 - 117.", "Gonzalez-Wevar CA, Hune M, Rosenfeld S, Saucede T, Feral J-P, Mansilla A, Poulin E. 2016 b. Patterns of genetic diversity and structure in Antarctic and sub-Antarctic Nacella (Patellogastropoda: Nacellidae) species. Biodiversity 17: 46 - 55."]}